The Cambridge companion to feminist theology - Parsons, Susan Frank (Cambridge companions to religion, 2002)
Feminist theology is a significant movement within contemporary theology. The aim of this Companion is to give an outline of feminist theology through an analysis of its overall shape and its major themes, so that both its place in and its contributions to the present changing theological landscape may be discerned. The two sections of the volume are designed to provide a comprehensive and critical introduction to feminist theology which is authoritative and up-to-date. Written by some of the main figures in feminist theology, as well as by younger scholars who are considering their inheritance, it offers fresh insights into the nature of feminist theological work. The book as a whole is intended to present a challenge for future scholarship, since it critically engages with the assumptions of feminist theology, and seeks to open ways for women after feminism to enter into the vocation of theology.